KOORDINASI PENYUSUNAN RENCANA KERJA PEMERINTAH DAERAH DI BAPPPPEDA KABUPATEN SUMEDANG - Kusdinar, Rika; Rukmana, Eka; Fadlilahudin; Yanti, Isni Yunita Ratna; Fitria, Mutya Dewi; Supriyadi, Teddy Asep (JRPA - Journal of Regional Public Administration, 2023)
The purpose of this study, among other things, is to find out Coordination in the Preparation of Regional Government Work Plans at BAPPPPEDA in Sumedang Regency. The research method used in this study is the qualitative method. Purchasing technique for research informants, namely Purposive Sampling. With research informants, namely the Head of PPEPD and six staff. The data collection technique used was library research and field studies consisting of observation, interviews and documentation. While the data management procedures in this study, namely Data Reduction, Data Display, Data Conclucion Drawing/Verification and Triangulation. Based on the research results, it can be concluded that employee coordination is seen from the leadership's responsibility, there is a process, regular arrangement of group efforts, the concept of unity of action, the purpose of coordination is quite good. - inhibiting factors inhibiting coordination: differences in orientation towards specific goals, differences in time orientation, differences in interpersonal orientation, differences in structural formality, which becomes difficult to unite and lack of facilities that inhibit differences of opinion used to support collaborative activities. Efforts to overcome coordination barriers : Basic management techniques , improve coordination potential , reduce the need for coordination.